2020
DOI: 10.1002/jcp.29595
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of terminal differentiation induced ncRNA (TINCR) suppresses proliferation and invasion in hepatocellular carcinoma by targeting the miR‐218‐5p/DEAD‐box helicase 5 (DDX5) axis

Abstract: Terminal differentiation induced ncRNA (TINCR), a newly identified lncRNA, has been found to be associated with different human cancers including hepatocellular carcinoma (HCC). However, little is known regarding the pathological mechanisms of TINCR in HCC progression. In this study, we confirmed that TINCR expression was upregulated in HCC tumors and cell lines, and high TINCR expression was associated with larger tumor size, advanced tumor node metastasis stage, and poor prognosis. Functionally, knockdown of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 38 publications
(38 reference statements)
1
13
0
Order By: Relevance
“…In HCC, two distinct studies showed association between over-expression of this lncRNA and induction of apoptosis via regulation of P53 and enhancement of cell proliferation via modulation of the miR-214-5p/ROCK1 axis, respectively [ 16 , 17 ]. Consistent with the latter study, depletion of this lncRNA in other HCC cell liens decreased oncogenic behavior through modulation of miR‐218‐5p/DDX5/AKT signaling [ 18 ].…”
Section: Cell Line Studiessupporting
confidence: 76%
See 3 more Smart Citations
“…In HCC, two distinct studies showed association between over-expression of this lncRNA and induction of apoptosis via regulation of P53 and enhancement of cell proliferation via modulation of the miR-214-5p/ROCK1 axis, respectively [ 16 , 17 ]. Consistent with the latter study, depletion of this lncRNA in other HCC cell liens decreased oncogenic behavior through modulation of miR‐218‐5p/DDX5/AKT signaling [ 18 ].…”
Section: Cell Line Studiessupporting
confidence: 76%
“…Notably, Kaplan-Meier analyses have shown correlation between expression levels of this lncRNA and patients survival in both directions. This issue has been reported in patients with lung cancer [ 14 , 15 ] and HCC [ 18 , 30 ]. Table 3 summarizes the results of studies which reported aberrant expression of TINCR in clinical samples.…”
Section: Human Studiesmentioning
confidence: 84%
See 2 more Smart Citations
“…Upregulation of Terminal differentiation-induced ncRNA (TINCR), small nucleolar RNA host gene 5 (SNHG5), and HCC-associated lncRNA (HCAL) has been identified in human HCC, and potential mechanisms by which they promote HCC have been implicated by in vitro studies [49][50][51]. However, more in-depth in vivo studies are required to validate these findings.…”
Section: Nuclear Paraspeckle Assembly Transcript 1 (Neat1)mentioning
confidence: 99%